The Man and the Statesman : The Correspondence and Articles on Politics - Bastiat, Frederic, 1801-1850 (Book collections on Project MUSE., 2011)
The main source for this translation is the seven-volume "Oeuvres completes de Frederic Bastiat", published in the 1850s and 1860s. The present volume, most of which has never before been translated into English, includes Bastiat's complete correspondence: 208 letters Bastiat wrote between 1819, when he was only 18 years old, until just a few days before his untimely death in 1850 at the age of 49. For contemporary classical liberals, Bastiat's correspondence will provide a unique window into a long-forgotten world where opposition to war and colonialism went hand-in-hand with support for free trade and deregulation. Bastiat's numerous letters to Richard Cobden, a Member of Parliament and best known today as the leader of the British Anti-Corn Law League, chronicle the profound effect the Anti-Corn League had on Bastiat. The League's success in mobilising a popular movement in England to pressure the British government into abolishing the very protectionist 'corn laws' in 1846, inspired Bastiat to emulate the League's success in France by starting his own free-trade movement. This volume also includes articles and other writings on politics and current events that showcase Bastiat's talent as a theoretician, a pamphleteer, a journalist, and a deputy (Member of Parliament) of the nascent French Second Republic. Together with the correspondence, the writings in this volume fill an important gap in our understanding of the lesser-known Bastiat, who, in just a few short years, made a profound impact on French intellectual and political life in Paris.